Salivary cortisol concentrations according to gender in the different stages of human development. A review of the literature - Gómez, Isaac Francisco (2021)
Salivary cortisol secretion (Corts) is an individual adaptation reflex to internal / external stressors, which involves several biological and social factors. The aim of this study was to perform a review on variations in Corts concentrations in relation to biological differences of sex and gender socialization in the different stages of human development. MEDLINE / PubMed and Google Scholar were used to search for scientific evidence. 20 original English-language articles published from 2010-2020 were selected, including clinical trials and observational studies. The relationship between Corts and gender was historically discussed considering evolutionary and biological aspects. However, it cannot be explained as a cause-effect view and depends on unique sociocultural factors, which in sensitive periods of human development alter the hypothalamic-pituitary-adrenal axis and condition coping with stress.